Discipline, Placement, Environment and Career Development on Job Satisfaction - Atik Silviati; Kartika Hendra TS; Istiatin Istiatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of work discipline, job placement, work environment, and career development on the job satisfaction of employees at the Food Security and Agriculture Office of Surakarta City. This research employs a quantitative approach using a survey method. The population in this study consists of all civil servant employees (ASN) at the Food Security and Agriculture Office of Surakarta City, with a total of 54 respondents determined using a total sampling technique. Data were collected through the distribution of questionnaires and analyzed using multiple linear regression with the assistance of the SPSS program. The results of the study show that, partially, work discipline, work environment, and career development have a positive and significant effect on employee job satisfaction. Meanwhile, job placement has a positive but not significant effect on job satisfaction. Simultaneously, the four variables have a significant effect on the job satisfaction of employees at the Food Security and Agriculture Office of Surakarta City. Therefore, improving work discipline, creating a conducive work environment, and implementing well-planned career development programs can increase employee job satisfaction, even though job placement does not have a significant effect. Keywords: work discipline, job placement, work environment, career development, job satisfaction.